Development of a cultural and contextual appropriate HIV self-management instrument using interpretive phenomenology and focus group cognitive interviews. (2020) - Crowley, Talitha; Van der Merwe, Anita; Skinner, Donald
Abstract: Qualitative methods are valuable to ensure the important cultural and contextual appropriateness of research instruments but not often used. Interpretive phenomenology (IP) and focus group cognitive interviews are well placed to inductively develop and refine items used to measure adolescent HIV self-management in a South African context. IP was used to situate the experiences of adolescents, caregivers and healthcare workers, as narrated in individual interviews and focus groups, in their social and cultural context. Components of adolescent HIV self-management were developed based on the participants' experiences, behavioural theory and literature. The components and items were further validated in focus groups using cognitive interviews to refine, revise and add items as suggested by the participants. This study contributes to qualitative research methods and the rigor of instrument development by unpacking how to use IP and focus group cognitive interviews meaningfully in instrument development.